Occupational Risk for Headache Disorders in Female Registered Nurses. A Retrospective Study - d'Ettorre, Gabriele; Baldassarre, Andrea (La Medicina del Lavoro, 2025)
Background: Prevention of headache disorders (HDs) among healthcare workers in hospital settings remains a challenge for organizations and employees worldwide. The goals of the present retrospective study were both to analyze the 1-year prevalence of any primary HDs among female registered nurses (RNs) employed in hospital settings and to investigate the relationship between occupational risk factors and HDs. Methods: We analyzed the occupational medicine database of RNs employed in a large hospital. The sample included 975 female RNs; the diagnostic criteria were based on the International Classification of Headache Disorders, 3rd edition (beta version). Results: One-year prevalence of any HD was 45.9%; tension-type headache (TTH) was the most commonly reported headache type (by 25.6% of participants), followed by migraine (17.5%). No association was found between the different headache types and work schedules; TTH was linked to age ≥40 years (OR=1.91; 95% CI=1.41-2.72), duration of service ≥15 years (OR=1.61; 95% CI=1.24-2.38), and number of night shifts >5 per month (OR=1.71; 95% CI=1.09-2.68). A high level of WRS was a significant predictor of TTH. Conclusions: We found a link between TTH and modifiable risk factors at both the individual and organizational levels. These findings suggest interventions in occupational settings to minimize the occurrence of TTH among RNs. Policy-makers and employers should implement preventive measures to reduce the incidence of HDs among RNs by minimizing modifiable risk factors associated with increased occupational risk.